2023
DOI: 10.1111/epi.17713
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament light, glial fibrillary acidic protein, and tau in a regional epilepsy cohort: High plasma levels are rare but related to seizures

Abstract: ObjectiveHigher levels of biochemical blood markers of brain injury have been described immediately after tonic–clonic seizures and in drug‐resistant epilepsy, but the levels of such markers in epilepsy in general have not been well characterized. We analyzed neurofilament light (NfL), glial fibrillary acidic protein (GFAP), and tau in a regional hospital‐based epilepsy cohort and investigated what proportion of patients have levels suggesting brain injury, and whether certain epilepsy features are associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Moreover, elevated GFAP levels in children with epilepsy were found to be a predictor for active seizures, and it was suggested that they could be used to monitor disease progression and severity for early identification of those with drug-resistant epilepsy and those who are in need of epilepsy surgery [34]. In line with these results, a recent study by Akel et al [89] in which increased levels of GFAP and NfL were found in patients with recent seizures in a large cohort of patients with epilepsy.…”
Section: S100bmentioning
confidence: 85%
“…Moreover, elevated GFAP levels in children with epilepsy were found to be a predictor for active seizures, and it was suggested that they could be used to monitor disease progression and severity for early identification of those with drug-resistant epilepsy and those who are in need of epilepsy surgery [34]. In line with these results, a recent study by Akel et al [89] in which increased levels of GFAP and NfL were found in patients with recent seizures in a large cohort of patients with epilepsy.…”
Section: S100bmentioning
confidence: 85%